(untitled) (Hanoi, 1995)
This book introduce about economic reforms and cocio-economic problems of development. Economic reforms and changes of economic structure in development process. Economic reforms and poverty alleviation in rural areas. Economic reforms and gender issues.
Keywords: Vietnam,Việt Nam,Việt Nam,Vietnam; Economic policy,Điều kiện kinh tế,Chính sách kinh tế,Economic conditions